2008
DOI: 10.2341/07-63
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Self-etch Adhesives to Enamel with Additional Phosphoric Acid Etching

Abstract: SUMMARYThis study evaluated the shear bond strength of self-etch adhesives to enamel and the effect of additional phosphoric acid etching.Seventy sound human molars were randomly divided into three test groups and one control group. The enamel surfaces of the control group (n=10) were treated with Syntac Classic (SC). Each test group was subdivided into two groups (each n=10). In half of each test group, ground enamel surfaces were coated with the self-etch adhesives AdheSe (ADH), Xeno III (XE) or Futurabond N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
50
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 19 publications
11
50
1
4
Order By: Relevance
“…[4][5][6] Pre-etching enamel with phosphoric acid has been shown to increase the bond strength of self-etch systems. [7][8][9][10][11][12][13][14] These observations suggest that reduced etching of enamel may compromise optimum bond strength and durability. Fatigue testing of enamel bonds has also shown that self-etch adhesives do not perform to the same level as traditional phosphoric acid conditioning systems.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Pre-etching enamel with phosphoric acid has been shown to increase the bond strength of self-etch systems. [7][8][9][10][11][12][13][14] These observations suggest that reduced etching of enamel may compromise optimum bond strength and durability. Fatigue testing of enamel bonds has also shown that self-etch adhesives do not perform to the same level as traditional phosphoric acid conditioning systems.…”
Section: Introductionmentioning
confidence: 99%
“…Because demineralization and resin infiltration occur simultaneously when using self-etch adhesives, dissolved hydroxyapatite crystals and smear layer remnants get incorporated into the polymerized resin layer. 6,8,11 Mild self-etch Adper SE Plus showed the highest bond strength values, while the acidic Adper Easy One showed the lowest values. This finding is consistent with previous literature which states that mild two-step self-etching primers usually performs better than acidic one step self-etching primers.…”
Section: Discussionmentioning
confidence: 99%
“…Bu tür adeziv sistemler smear tabakasını çözebilmek ve dentini demineralize edebilmek için yüksek oranda su içermektedir [66][67][68][69] . Bu aşırı hidrofilik özellik, polimerizasyondan sonra yarı geçirgen bir membran gibi davranıp dentinden su geçişine izin vererek hidrolitik bozulmaya neden olan su kabarcıklarını oluşturmaktadır [70][71][72][73] .…”
Section: B) Tek Aşamalı Se Adeziv Sistemlerunclassified